PROSES HIDROLISIS SAMPAH ORGANIK MENJADI GULA DENGAN KATALIS ASAM KLORIDA - Zainal Arifin, Dedy Irawan (Jurnal Teknik Kimia, 2012)
Hydrolysis is one of the most important stages of bioethanol production made ​​from organic waste. Hydrolysis with dilute hydrochloric acid concentration was varied from 0.25-1% with a temperature of 120-180oC and time of 15-120 minutes. Reactant ratio 1:6 between organic waste and dilute hydrochloric acid for every stage hydrolysis was reacted in a batch reactor system. The sugars concentrations in the hydrolyzate were then analyzed by Nelson-Somogyi method. The results showed that the best conditions for hydrolysis was found at temperature of 120oC, catalyst concentration of 0.75%, time of 30 minutes and the pressure of 4 bar with the sugar concentration of 29.34 mg/mL and the yield of 13.09%. Key word : hydrochloride acid , hydrolysis, sugar concentration, yield